South Bank Exhibition - poster, 1951 (London, 1951)
1951 1951-1960 "South Bank Exhibition - poster, 1951" [BW0223], 1951, Trades Union Congress Educational poster published by the Bureau of Current Affairs showing a model of the Festival of Britain on London's South Bank. The Festival of Britain was an attempt to give the post-war period a feeling of recovery and progress and to promote better-quality design in the rebuilding of British towns and cities following the war. The Labour Party's Deputy Leader, Herbert Morrison, described it as "a tonic for the nation".